2002
DOI: 10.1038/sj.leu.2402620
|View full text |Cite
|
Sign up to set email alerts
|

CD34+ or CD34−: which is the more primitive?

Abstract: Remarkable progress has been achieved in the characterization and isolation of primitive hematopoietic stem cells (HSC). HSC represent a very small subset of hematopoietic cells and provide self-renewal, possess differentiation capacity and allow a constant supply of the entire hematopoietic cell spectrum. Until recently, CD34 has been used as a convenient marker for HSC, since CD34 ؉ cells have been shown to possess colony-forming potential in short-term assays, maintain long-term colony-forming potential in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 77 publications
(95 reference statements)
3
39
0
1
Order By: Relevance
“…Recent studies have shown that CD34 Ϫ HSCs exist as well. 36,37 These CD34 Ϫ cells also possess HSC-specific characteristics, including the ability for hematopoietic engraftment. 36,37 This brings up the question as to whether the NPM1 mutant AML cells in fact represent a more primitive population of HSCs with a HOX gene signature.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that CD34 Ϫ HSCs exist as well. 36,37 These CD34 Ϫ cells also possess HSC-specific characteristics, including the ability for hematopoietic engraftment. 36,37 This brings up the question as to whether the NPM1 mutant AML cells in fact represent a more primitive population of HSCs with a HOX gene signature.…”
Section: Discussionmentioning
confidence: 99%
“…CD34 has been long believed to be an HSC marker, but recent data revealed that the expression of CD34 is reversible and regulated by HSC activation. 22,23 Although the functional significance of CD34 remains unclear, L-selectin on leukocytes and E-selectin on vascular endothelium are putative ligands of CD34. [36][37][38] Our preliminary data showed both the CD34 þ and CD34 À fractions of SUG cells could similarly reconstitute leukemia in NOG mice.…”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20] Intravenous injection of human leukemia cells into non-obese diabetes/severe combined immunodeficiency (NOD/SCID) mice, which is now the most common and most nearly physiological method to identify human HSCs in vivo, shows that leukemia cells expressing primitive cell surface makers such as CD34 þ and CD38 À can repopulate NOD/SCID mice regardless of the acute myeloid leukemia (AML) type. [21][22][23] The concept of leukemia stem cells (LSCs) may change current notions about how leukemia develops and how leukemia should be treated. However, the microenvironment for LSC is not yet well understood.…”
Section: Introductionmentioning
confidence: 99%
“…Modifications in previously described isolation protocols may also account for the variability of engraftment in immunocompromised animal models [17]. Due to the need to find an optimized population, we have developed a reproducible strategy for primitive cell harvest.…”
Section: ® Original Articlementioning
confidence: 99%